Digitalization of Design and Machining Processes of Wood Carving Products Using CAD/CAM/CNC Technologies for Preservation of Minangkabau Culture - Islami, Fadli; Sutanto, Agus (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2024)
The preservation and development of Minangkabau wood carvings are facing significant challenges due to a decline in skilled carvers and the deterioration of existing artworks caused by natural factors and aging. If these trends continue, the unique motifs of Minangkabau carving risk becoming extinct. A digital preservation initiative is essential to document and store these motifs for future generations. This study proposes the application of CAD/CAM/CNC technologies to facilitate this preservation effort. By digitizing original carvings into 2D and 3D formats, this research aims to create accessible digital archives of Minangkabau motifs. Given the vast array of available designs and motifs, this research will focus on four selected motifs based on their complexity and philosophical significance. These motifs will be produced using traditional manual carving and modern CNC methods, specifically the V-Carving technique. The processing time required for each method will be documented throughout the manufacturing process to evaluate their respective advantages and drawbacks. The research findings show that although the CNC method can significantly improve efficiency, requiring an average processing time three times faster than the manual method, it may not fully replicate the skill and precision of traditional carving, especially in achieving intricate relief details and unique motif shapes. This approach seeks to preserve cultural heritage while enhancing the understanding of integrating traditional artistry with contemporary technology.